GROWTH HACKING AS A TOOL FOR ENSURING THE DEVELOPMENT MODEL OF INNOVATIVE MARKETING IN AN INDUSTRIAL ENTERPRISE - YAKIVCHENKO, Andriі (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the concept of Growth Hacking as an advanced marketing methodology designed to accelerate business growth in industrial enterprises by leveraging digital technologies, experimental testing, behavioral analytics, and automation tools. In the era of rapid digital transformation and economic uncertainty, traditional marketing approaches are becoming less effective, necessitating the adoption of more adaptive and technology-driven strategies. Growth Hacking, originally popularized in the technology startup ecosystem, has now evolved into a strategic tool for optimizing marketing processes, improving customer engagement, and enhancing business scalability in various industries, including manufacturing, aviation, and energy sectors.The study identifies key Growth Hacking elements, including data-driven decision-making, customer segmentation, UX optimization, gamification, viral marketing techniques, A/B testing, and the integration of artificial intelligence for automated personalization. Special emphasis is placed on the behavioral economics aspects that influence consumer decision-making, enabling businesses to fine-tune their marketing strategies by leveraging cognitive biases, social proof, scarcity effects, and emotional triggers.Through an in-depth analysis of successful case studies, this paper examines how global industry leaders like Netflix and Dropbox have implemented Growth Hacking strategies to gain a competitive edge. Netflix has utilized advanced AI algorithms, content recommendation engines, and behavioral targeting to increase user retention and drive engagement. Dropbox, on the other hand, successfully applied referral-based growth models and frictionless onboarding techniques to rapidly expand its user base while minimizing customer acquisition costs.Building on these insights, the article presents a conceptual model for implementing Growth Hacking within strategic marketing management for industrial enterprises. This model integrates digital tools, consumer behavior analysis, and agile methodologies to optimize business operations and ensure sustainable growth. The research findings suggest that Growth Hacking can significantly enhance the competitiveness of industrial enterprises by reducing marketing expenses, increasing return on investment (ROI), and strengthening long-term customer relationships. Furthermore, the study emphasizes the role of Growth Hacking as a key driver for economic recovery in the post-war period, particularly for Ukrainian enterprises seeking innovative approaches to market expansion and industrial revitalization.In conclusion, this paper highlights the transformative potential of Growth Hacking for industrial enterprises, showcasing its ability to bridge the gap between traditional marketing strategies and digital-first growth models. The study provides practical recommendations for integrating Growth Hacking principles into strategic decision-making processes, ensuring that industrial firms can navigate market uncertainties, capitalize on emerging opportunities, and achieve sustainable competitive advantages in the global business environment.
Keywords: innovative marketing; marketing tools; Growth-Hacking; mechanism; sustainable development; management; digital technologies; gamification; behavioral economics; automation; industrial enterprises; competitiveness